Moisture- responsive controlled-release herbicide system using guar gum and nano cellulose for sustainable weed management in rainfed agriculture - Prasanna, Jakku; Marimuthu, S.; Gowtham, G.; Shanmuganathan, K.; Lakshmanan, A.; Chandana, Pebbeti; Karthikeyan, S.; Somasundaram, E. (Results in Engineering, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Weed management poses a significant challenge in rainfed agricultural system, with chemical control being the predominant strategy due to its expeditious nature. However, the efficacy of herbicides in these systems is heavily dependent on optimal soil moisture, making the application of pre-emergence herbicides difficult due to erratic rainfall patterns. Sudden rainfall events post-sowing can result in sticky or muddy fields, complicating the application process and leading to infrequent use of pre-emergence herbicides in rainfed agriculture. To address these challenges, an innovative approach was developed involving the herbicide molecules entrapment in hydrogel matrices synthesized from biopolymers. This study focuses on the design and preparation of atrazine-loaded hydrogel using guar gum and nanocellulose, aimed at managing weeds in maize crops, which are prevalent in rainfed regions. The paper details the protocol for synthesizing the hydrogels and entrapment of atrazine, characterizing the formulations, and conducting pot validation trials to assess phytotoxicity and weed control efficacy compared to commercial atrazine application. The results demonstrated high water retention capacities and entrapment efficiency of the hydrogel for preferable application. FTIR analysis confirmed the presence of atrazine at 802 cm<span style="box-sizing: border-box; margin: 0px; padding: 0px; line-height: 0; position: relative; vertical-align: baseline; top: -0.5em; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif;">-1<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> and other excipients in the encapsulated formulations, while XRD analysis verified the presence of nanocellulose. The release pattern indicated a sustained and controlled release of atrazine from the hydrogels over 40 h in-vitro studies, compared to the complete dissolution of pure atrazine within three hours. Screening trial further validated the crop safety and improved weed control efficiency of the entrapped formulations relative to commercial atrazine. The encapsulated formulations using biopolymer-based hydrogels show promise as a viable alternative for weed management in rainfed agriculture, offering controlled herbicide release and improved application efficiency under variable moisture conditions.